GERAKAN PEMBARUAN SAYID AHMAD KHAN - Dulumina, Gunawan B. (Hunafa: Jurnal Studia Islamika, 2005)
Sayid Ahmad Khan is an Islamic modernist of  India. He is a typical figure who is very enthusiastic in combating illiteracy of  Muslims of India. Therefore, he tries to reinterpret the Islamic doctrines in accordance with the development of science and technology. However, because of  his radical Islamic thought,  he has to accept  criticism from conservative Muslims of India. This article tries to discuss his steps in encouraging Muslims of  India to positively welcome modernism ideas.Kata kunci : Pembaruan, Sayid Ahmad Khan, Islam